L‐type amino acid transporter‐1 and CD98 expression in bone and soft tissue tumors. (1st July 2015) - Koshi, Hiromi; Sano, Takaaki; Handa, Tadashi; Yanagawa, Takashi; Saitou, Kenichi; Nagamori, Shushi; Kanai, Yoshikatsu; Takagishi, Kenji; Oyama, Tetsunari
<x xml:space="preserve">Abstract</x> L‐type amino acid transporter‐1 (LAT1) is expressed in many cancers. We examined LAT1 and CD98 expression immunohistochemically in surgically resected specimens of various bone and soft tissue tumors. Out of 226 cases, 79 (35%) were LAT1+ and 95 (42%) were CD98+. In bone tumors, LAT1 was highly expressed in osteoblastoma (89%), chondrosarcoma (50%), and osteosarcoma (60%); in soft tissue tumors, LAT1 was highly expressed in rhabdomyosarcoma (80%), synovial sarcoma (63%), Ewing's sarcoma (60%), epithelioid sarcoma (100%) and angiosarcoma (100%). In malignant soft tissue tumors, LAT1 expression was associated with higher histological grade. High CD98 expression was seen in many bone tumors of intermediate and high malignancy. Among soft tissue tumors, CD98 was expressed in tendon sheath giant cell tumor and malignant peripheral nerve sheath tumor (57%), Ewing's sarcoma (50%) and undifferentiated sarcoma (64%). Some of the malignant soft tissue tumors expressed both LAT1 and CD98. This study showed that LAT1 and CD98 was expressed in many malignant and intermediate bone tumors, and some malignant soft tissue tumors.